How Poverty, Malnutrition and other Socioeconomic factors affect maternal health: a quantitative study from Lahore Pakistan - Saba Ilyas A. Malik, Laila Shahzad, Samar Hussain, Saima Qurban, Humaira Durrani, Muhammad Naim Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Low socioeconomic status can increase the risk of unhealthy pregnancy results. In Pakistan malnutrition is a leading factor affecting health of pregnant females along fetus and is one of main cause of high maternal morbidity and mortality. One child out of four is victim of malnutrition here. Objective: The basic objective of this study is to determine the relationship between poverty and maternal health. There are many indicators that come under the umbrella of poverty which affects maternal heath such as socio-demographic, physical and mental wellbeing, medical and nutritional profile. Keeping these indicators under consideration, it becomes feasible to understand whether and how poverty affects maternal health. Methodology: A survey was conducted from May 2020 to end of June 2020 through a questionnaire consisting of 33 items. Population size was 200. It was hypothesized that 50% of the population will be under health stress. Important findings: The data collection and analysis showed 54.5% of population under study was health compromised due to poverty or low socioeconomic status. 61.8% of population specified improper diet as health issue that was the major reason behind their abortion/miscarriage/preterm labor. 57.2% of pregnant women were not satisfied with their diet plan. 48.6% of population faced psychological issues during gestation period and 59.3% of population faced financial crisis during pregnancy. Conclusion: It was concluded that poverty had negative influence on maternal health and is indicated by different factors like poor diet, poor physical and mental wellbeing, which resulted in adverse maternal outcomes. This issue needs to be addressed and health care services should be made equally available for all women at least cost. Keywords: poverty; low socioeconomic status; maternal health risk; pregnancy outcomes, risk-management